UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING TAHUN 2018-2021 - Uswatun Hasanah; Lita Permatasari; Ida Subaida (Fakultas Ekonomi dan Bisnis, 2023)
Food and beverage companies are one of the business sectors that continue to experience growth. Along with increasing number growth population in Indonesia, the total demand for food and beverages continue increase. The purpose of this research is to analyze and test the company’s size and Leverage on company value in Food Companies and Beverages listed on the IDX through the dividend policy. Data analysis and hypothesis testing in this study using the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application, shows the size of the company has a positive and significant effect on dividend policy. Leverage has a positive effect but not significant on dividend policy. Company size has a positive effect but not significant to company value. Leverage has a negative and significant effect on company value. Dividend policy has a positive effect but not significant to company value. Indirect hypothesis test results shows that company size has a negative effect but not significantly to the value of the company through the dividend policy. Leverage positive but not significant effect on company value through Dividend policy.